"A forgotten generation": medical care for disabled veterans of the First World War in independent Ireland. Issue 2 (3rd April 2021) - Farrell, Anthony
ABSTRACT: The First World War is often regarded through the prism of commemoration and remembrance of the dead and missing of that conflict, a lost generation. The men and women that returned, especially those who were disabled by their wartime service can be considered a Forgotten Generation. Literature about casualties of the war tend to focus on shell-shock also known as neurasthenia. The physically injured tend to be overlooked, despite numbers that far outnumber neurasthenic cases. The British Ministry of Pensions established clinics and hospitals in Ireland to care for both physical and psychological casualties. After the war, and the later establishment of the Irish Free State, these facilities were retained for the continuing treatment of veterans who had been awarded a disability pension for wounds, injuries or illnesses that were directly attributable to their war-time service. Internal British government correspondence described the services as an Imperial Obligation to be maintained until the last surviving disabled veteran had passed away.